Analisis Makna Ganda Menggunakan Pendekatan Semiotik Saussure dalam Mengkritik Cerpen Pantura Karya Danarto - Syahputri, Sri; Saragi, Tasya Amelia; Hutabarat, Sani; Silitonga, Erika Cyntia P.; Siburian, Mieke Angelika; Zafira, Putri Alicya; Sipayung, Atika Wasilah (Asosiasi Ide Bahasa Kepri, 2025)
This study aims to analyze the meaning implied in the short story Pantura by Danarto through semiotics approach Ferdinand de Saussure. Short stories as imaginative literary works contain messages of life conveyed through connotative language that often cannot be understood literally. In short stories Pantura, Danarto convey a variety of spiritual and social values through symbols and linguistic signs that are full of meaning. This study uses descriptive qualitative methods with a case study approach to reveal the double meaning of the symbols used in the short story. Saussure's semiotic theory of sign as the result of the relationship between signifier and signified became fundamental in analysis. The results showed that the Pantura short story not only describes the flood disaster physically, but also a metaphor of a small apocalypse in life, a spiritual test, and a form of reflection on the social conditions of the community. The character “I” in the short story shows the attitude of firm faith and sincerity in accepting fate, which is inversely proportional to the attitude of modern society which tends to blame the situation when facing a disaster. Symbols such as weather, floods, rafts, and money are used to represent inner conflict, sincerity, and the wonders of God in people's lives. This research contributes to the study of literature by showing that the semiotic approach is able to reveal the depth of meaning in literary works, as well as being a reflection tool for readers to understand spiritual and human values in the current social context. Thus, this study enriches the reader's perspective in appreciating and interpreting literary works in greater depth.